Celastrol: An Update on Its Hepatoprotective Properties and the Linked Molecular Mechanisms - Li, Mengzhen; Xie, Faren; Wang, Lu; Zhu, Guoxue; Qi, Lian-Wen; Jiang, Shujun (Frontiers in Pharmacology, 2022)
The liver plays an important role in glucose and lipid homeostasis, drug metabolism, and bile synthesis. Metabolic disorder and inflammation synergistically contribute to the pathogenesis of numerous liver diseases, such as metabolic-associated fatty liver disease (MAFLD), liver injury, and liver cancer. Celastrol, a triterpene derived from Tripterygium wilfordii Hook.f., has been extensively studied in metabolic and inflammatory diseases during the last several decades. Here we comprehensively review the pharmacological activities and the underlying mechanisms of celastrol in the prevention and treatment of liver diseases including MAFLD, liver injury, and liver cancer. In addition, we also discuss the importance of novel methodologies and perspectives for the drug development of celastrol. Although celastrol has been claimed as a promising agent against several metabolic diseases, both preclinical and clinical studies are highly required to accelerate the clinical transformation of celastrol in treating different liver illness. It is foreseeable that celastrol-derived therapeutics is evolving in the field of liver ailments.